2007
DOI: 10.1007/s10725-007-9192-0
|View full text |Cite
|
Sign up to set email alerts
|

Spectral composition of irradiation regulates the cell growth and flavonoids biosynthesis in callus cultures of Saussurea medusa Maxim

Abstract: Cell growth, flavonoids biosynthesis and L-phenylalanine ammonia-lyase (PAL) activity were studied in callus cultures of Saussurea medusa Maxim. under different types of spectral radiance. After 21 days, red light significantly improved the callus growth, but inhibited the biosynthesis of flavonoids in callus cultures. However, blue light was found to enhance the biosynthesis of flavonoids, although callus growth under this spectrum was comparable with that under white and other coloured spectra, such as green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…2). This is in agreement with previous reports, indicating the stimulatory effect of blue light on the accumulation of plant phenolics in in vitro cultures, with examples including flavonoids in Saussurea medusa calli (Guo et al 2007) and phenolic acids in shoots of Ruta graveolens (Szopa et al 2012). Unfortunately, in the present work the production of the most valuable metabolites (i.e.…”
supporting
confidence: 94%
“…2). This is in agreement with previous reports, indicating the stimulatory effect of blue light on the accumulation of plant phenolics in in vitro cultures, with examples including flavonoids in Saussurea medusa calli (Guo et al 2007) and phenolic acids in shoots of Ruta graveolens (Szopa et al 2012). Unfortunately, in the present work the production of the most valuable metabolites (i.e.…”
supporting
confidence: 94%
“…Although no previous information is available on the effects of light quality on these phenolic compounds, similar results have been reported for other phenolics under red light. Guo et al (2007) showed that flavonoid biosynthesis in Saussurea medusa callus cultures was inhibited by red light irradiation. Similarly, leaves of Ocimum basilicum (Shoji et al, 2011) irradiated by red light were found to contain lower concentrations of chicoric acid.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the phenolic content of buckwheat (Fagopyrum esculentum) leaves was significantly increased when the plants received a combination of red, green, and blue light (Hossen, 2007). In Saussurea medusa, a positive correlation was found between blue LEDs and the biosynthesis of flavonoids, whereas red LEDs inhibited flavonoid biosynthesis (Guo et al, 2007).…”
mentioning
confidence: 99%
“…Cultured cells could produce secondary metabolites, and the quantity of such a useful ingredient varies with the culture environment, including the kind and strength of light irradiating cultured cells (Guo et al, 2007;Ouyong et al, 2003). In this study, we expected to isolate the allelochemicals via abundant biosynthesis, so they could be released into the solvent by regulating the type and strength of light irradiating the calluses, because it is evident that asparagus calluses possess allelopathic activities.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that artemisinin contents were increased under red light in the culture of hairy roots in Artemisia annua (Wang et al, 2001). In Cistanche deserticola and Saussurea medusa, phenylethanoid glycoside content (Ouyang et al, 2003) and the accumulation of flavonoid (Guo et al, 2007) could be promoted, respectively, in individual calluses by irradiation with blue light. These findings led us to anticipate that the cultures would actively produce allelochemicals by irradiation with a specific wavelength range of light.…”
Section: Introductionmentioning
confidence: 99%